Types and Density of Aquatic Plant in Lubuk Siam Lake Lubuk Siam Village Siak Hulu Sub-Regency Kampar Regency Riau Province - Antoni '; Efawani '; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Lubuk Siam Lake is one of the oxbow lakes in the Lubuk Siam Village, SiakHulu Sub-regency, Kampar Regency, Riau Province. This lake is overgrown by varioustypes of aquatic plants and almost cover the surface of the lake. This condition hampersthe fishing activities in the lake. This research aims to discover the types and density ofthe aquatic plant in Lubuk Siam Lake and it was conducted on February to March 2015.Field sampling was done 2 times, a month period. The plants were then identified basedon Van Steenis (1981).Results shown that there were 7 species of aquatic plants present in the LubukSiam Lake and they are belonged to 4 classes, 7 families. They are Eichhornia crassipes,Salvinia natans, Ipomoea aquatica, Cyperus sp., Paspalum sp., Pandanus sp., andNephrolepis sp. The most common plant is Salvinia natans (61-71 organisms/m2,relative density 55.94-57.13 %), while the rarest was Ipomoea aquatica (4.5-7organisms/m2, relative density 3.48-6.47 %). In general, the relative density of aquaticplants in the Lubuk Siam Lake can be categorized as rare to dense.Keywords: Lubuk Siam Lake, Aquatic Plant, Density